(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Thyroid carcinoma is a highly aggressive tumor, often giving rise to recurrent cancer and metastatic cancer even after the surgical treatment. Early detection of thyroid cancer is essential for improving long term treatment and patient survival rate. Objective: To compare the diagnostic accuracy of PET/ CT with the conventional methods and radioactive iodine scans in the management of thyroid cancer. Methodology: Published reports of comparing the diagnostic accuracy of PET/ CT with the conventional methods and radioactive iodine scans in the management of thyroid cancer were identified by a systematic search of Google Scholar, PubMed, Research Gate, Springer and the Sci Hub, supplemented with citation tracking. From 1001 initially identified studies, only 13 studies met the inclusion criteria after screening and duplicate removal. These studies compared the diagnostic accuracy of PET/ CT with the conventional methods and radioactive iodine scans in the management of thyroid cancer, using standard statistical measures, typically at a 95% confidence level. Results: The literature reviewed reveals that PET/CT imaging, especially when using 18F-FDG, is important in managing thyroid cancer especially when the conventional imaging tools such as radioactive iodine (RAI) scans and ultrasound fail to clearly indicate the condition. PET/CT has a good diagnostic accuracy in the diagnosis of recurrent or metastatic disease in patients with Thyroglobulin-Elevated Negative Iodine Scintigraphy (TENIS) with spilling sensitivity and specificity to 94.3 percent and 78.4 percent, respectively. It has better sensitivity in detecting metastases that are at a distance particularly that of poorly differentiated and anaplastic thyroid carcinomas where there is reduced avidity to iodine and standard scans are ineffective. Although RAI whole-body scanning is still useful as an initial stage diagnostic procedure and in detection of remnants in differentiated thyroid cancers (DTCs), PET/CT has added accuracy in localizing metabolically active disease especially in follow-up of postoperative patient or in biochemical recurrence when RAI scans are negative. Moreover, it has been seen that 18F-FDOPA PET/CT is more sensitive in enlightening the recurrence of medullary thyroid carcinoma (MTC), particularly in those cases where the level of calcitonin is high in the patients. In general, PET/CT is adding value to the existing imaging protocol because of yielding metabolic information contributing to better staging and planning of the treatment decisions and ultimately in enhancing the overall results of the patient in aggressive/biochemically active thyroid cancers, which do not demonstrate well on conventional modalities. Conclusion: PET/CT scanning exhibits high sensitivity and specificity values in the diagnosis of local recurrence and metastases in post- surgical patients with medullary thyroid carcinoma. Furthermore, based on a comparative analysis of18F-FDG and GA68-DOTATE, it appears that these radiotracers are particularly sensitive and reliable for highlighting MTC, and it was found that there were no statistical differences in terms of sensitivity and specificity. Therefore, these two modalities appear to be complementary in monitoring MTC patients.